Investigating the need for antibiotic supplementation to the extender used for semen cryopreservation in collared peccaries - Moreira, Samara S. J.; Santos, Caio S.; Castelo, Thibério S.; Bezerra, Luana G. P.; Praxedes, Érica C. G.; Matos, Tayná M.; Souza-Junior, João B. F.; Feijó, Francisco M. C.; Comizzoli, Pierre; Silva, Alexandre R. (Frontiers in Veterinary Science, 2022)
The objective was to investigate the effects of semen freezing extender supplementation with antibiotics on bacterial load of semen samples, sperm functional and morphological metrics in the collared peccary. Fresh ejaculates from 10 males were extended in Tris-egg yolk-glycerol supplemented or not (control) with streptomycin-penicillin (SP; 1 mg/mL - 1000 IU/mL) or gentamicin (70 μg/mL) and cryopreserved in liquid nitrogen. Bacterial load, sperm motility patterns, morphology, membrane functionality and integrity, mitochondrial activity, chromatin integrity and sperm-binding ability were evaluated in fresh and frozen-thawed samples. Regardless of the use of antibiotics, the sole cryopreservation provoked a significant decrease (P < 0.05) in bacterial load compared to fresh samples (from average values > 1 x 106 CFU/mL to <0.4 x 106 CFU/mL). Post-thawing sperm kinetic parameters were not affected by the absence or presence of different antibiotics, except for beat cross frequency that was significantly (P < 0.05) impaired by SP supplementation compared to the group without antibiotics. After thawing, sperm morphology, membrane functionality and integrity, and mitochondrial activity were also not affected by the presence or absence of antibiotics; however, a significant decrease was observed in the group without antibiotics (P < 0.05) in comparison to fresh samples. Regarding sperm-binding ability, there were no differences among the different groups. While collared peccary semen could be efficiently cryopreserved in the absence of antibiotics in the extender, the use of both gentamicin or the streptomycin-penicillin combination is recommended as effective antibiotic supplementation for a further control of bacterial loads without affecting sperm parameters.